A Sociolinguistic Analysis of the Registers of the Street Hawkers in Dhaka - Tanvir Hassan Anik; Mohammad Golam Mohiuddin; Md. Didarul Islam; Muhammad Kamruzzaman (Crossings)
This study examines the distinctness of registers shared as a part of communication by the street hawkers in Dhaka. The reasons for studying these registers are to investigate their different jargons, why they use them while selling their products, and what they mean through them. It also explores the effectiveness of their registers in their communication. By adopting the qualitative method, the researchers have interviewed 40 street hawkers, recorded their conversations and some distinctive vocabularies for over a month, and found some striking meaningful registers they share in this profession. The results show that they use these specific registers before the customers to make communication comfortable and smooth. They also share these jargons to hide the real meaning from customers, to make fun of them, to discourage their fellow hawkers from promptly selling a product, to get rid of some particular customers, and sometimes even to cheat and provoke them. The findings of the study are discussed carefully to draw the attention of language users, planners, and policymakers. One of the important reasons for choosing the street hawkers was to concentrate on the professional language variation of an underprivileged community in Dhaka.